Changes in hearing function and intracochlear morphology after electrode array insertion in minipigs. - Du, Haiqiao; Li, Jianan; Chen, Zhifeng; Gao, Yun; Yang, Xiao; Yuan, Shuolong; Wang, Qian; Guo, Weiwei; Chen, Wei; Dai, Pu; Yang, Shiming (Acta Oto-Laryngologica, 2024)
In temporal bone specimens from long-term cochlear implant users, foreign body response within the cochlea has been demonstrated. However, how hearing changes after implantation and fibrosis progresses within the cochlea is unknown. To investigate the short-term dynamic changes in hearing and cochlear histopathology in minipigs after electrode array insertion. Twelve minipigs were selected for electrode array insertion (EAI) and the Control. Hearing tests were performed preoperatively and on 0, 7, 14, and 28 day(s) postoperatively, and cochlear histopathology was performed after the hearing tests on 7, 14, and 28 days after surgery. Electrode array insertion had a significant effect for the frequency range tested (1 kHz–20kHz). Exudation was evident one week after electrode array insertion; at four weeks postoperatively, a fibrous sheath formed around the electrode. At each time point, the endolymphatic hydrops was found; no significant changes in the morphology and packing density of the spiral ganglion neurons were observed. The effect of electrode array insertion on hearing and intracochlear fibrosis was significant. The process of fibrosis and endolymphatic hydrops seemed to not correlate with the degree of hearing loss, nor did it affect spiral ganglion neuron integrity in the 4-week postoperative period.